2023
DOI: 10.1039/d3ta02088f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the limits to short-range order suppression in many-component disordered rock salt lithium-ion cathode materials

Abstract: Suppressing unfavourable short-range ordering in disordered rock salt lithium-ion cathode materials is seen as a key research goal on their route to commercialisation. In this study we use cluster-expansion-driven Monte...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…8–12 Several transition metals such as Mn, Ti, V, and Cr have been utilized to synthesize DRXs with capacities of up to 300 mA h g −1 . 13–17 Transition metal cation mixing, 11,18 short-range ordered structure analysis, 19–22 and the Li + migration mechanism 23–26 are highly researched to activate the high capacity and improve the rate performance of DRXs. Recently, Konuma et al reported a “near dimensionally invariable” material Li 8/7 Ti 2/7 V 4/7 O 2 , which was encapsulated in Li 6 PS 5 Cl-based ASSBs using a PEEK mold and achieved a capacity of 300 mA h g −1 at a high operating pressure of 200 MPa and a current of 0.2 C (60 mA g −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…8–12 Several transition metals such as Mn, Ti, V, and Cr have been utilized to synthesize DRXs with capacities of up to 300 mA h g −1 . 13–17 Transition metal cation mixing, 11,18 short-range ordered structure analysis, 19–22 and the Li + migration mechanism 23–26 are highly researched to activate the high capacity and improve the rate performance of DRXs. Recently, Konuma et al reported a “near dimensionally invariable” material Li 8/7 Ti 2/7 V 4/7 O 2 , which was encapsulated in Li 6 PS 5 Cl-based ASSBs using a PEEK mold and achieved a capacity of 300 mA h g −1 at a high operating pressure of 200 MPa and a current of 0.2 C (60 mA g −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heteroanionic materials, which contain two or more anionic species, offer compositional and structural flexibility not found in otherwise analogous homoanionic materials. As such, controlling the relative stoichiometries and crystallographic arrangements of the anion species in heteroanionic materials allows their properties to be tuned. , This compositional and structural versatility means that heteroanionic materials find applications across a range of critical technologies, including thermoelectrics, photocatalysis, , and energy storage. …”
Section: Introductionmentioning
confidence: 99%
“…This could be inspired by the efficient methods for selecting training data for conventional cluster expansions and should be highly relevant for more complex compositions. For these, conventional cluster expansion modeling is already faced with challenges due to the many compositional degrees of freedom, and we expect this methodology to face similar challenges. Furthermore, improvements may be observed with other types of machine learning architecture such as equivariant neural network potentials. , …”
mentioning
confidence: 99%